Bibliometric Analysis of Gamification-Based Learning Media - Arthur Muhamad Taufan Herlambang (CV. Media Inti Teknologi, 2024)
This research aims to analyze the Gamification learning method's impact and the trends in research regarding Gamification. The research method used is a qualitative descriptive method using a bibliometric approach starting from defining the keywords “Gamifikasi (Gamification)” and ”Jurnal” in the Publish or Perish application using the Scopus database. Article selection was carried out based on predetermined categories and a total of 21 articles were obtained that fit the predetermined categories. Then the articles obtained are compiled based on metadata using the Mendeley and the Vosviewer application to create visualizations. The research results show that based on bibliometric analysis gamification has been categorized into ten clusters. The application of gamification in the education sector is needed in the learning process to support the learning process and improve students' skills or learning outcomes at the upper secondary level. Previous research also shows that the use of gamification-based learning media in the world of education, more precisely at the high school level, provides benefits or influence for both teachers and students. The results of the bibliometric research that has been carried out show that there are quite a lot of articles discussing gamification-based learning media on the Scopus platform and are already in the top Quartile, namely Quartile 1. However, for articles discussing gamification-based learning media, especially those that originating from Indonesia, there are still very few found there. Therefore, the research results show that the topic of gamification-based learning media, especially in Indonesia, is still very amenable to research and discussion in the future.